(untitled) (المجلة الدولية للبحوث العلمية, 2024)
Option of sight is an Islamic theory assigned to regulate contractual relationships. It came from a Prophetic statement narrated from the Prophet Mohammad (peace be upon him) and became a part of the rules which regulate the relationship between the parties of the contract of sale. It gives the buyer who did not see the goods at the time of conclusion of the contract the right to rescind it when he sees them. This option is regulated in several Islamic countries as these countries depend, basically, on Islamic legislation as a reference and as a historical source for their laws. Although it is not regulated in CISG, it may have role to govern an international sale if the applicable law chosen by the parties deal with such matters. Thus, it is within the aim of this paper to explore in depth the role of the option of sight in protecting the buyer in the international sale contract. It clarifies the meaning of the option and shows how it keeps the buyer away from deception that may come from the seller. The paper, indeed, includes the sale in which the buyer sees the goods via the e-means. The study comes with a result that; if this theory is embodied in the international conventions that regulate the international commerce, it will have an important role to prevent the deception and dishonesty that may happen in practice.